Effect of microvascular invasion on the postoperative long-term prognosis of solitary small HCC: a systematic review and meta-analysis. Issue 8 (August 2019) - Chen, Zhen-Hua; Zhang, Xiu-Ping; Wang, Hang; Chai, Zong-Tao; Sun, Ju-Xian; Guo, Wei-Xing; Shi, Jie; Cheng, Shu-Qun
Abstract: Background: The effect of microvascular invasion (MVI) on the postoperative long-term prognosis of solitary small hepatocellular carcinoma remains controversial. We compared the long-term outcomes of MVI-positive and MVI-negative groups of patients with solitary small hepatocellular carcinoma. Methods: The PubMed, EMBASE, Cochrane Library, VIP, Wan Fang, and Sino Med databases were systematically searched to compare the long-term outcomes of MVI-positive and MVI-negative groups of patients with solitary small hepatocellular carcinoma from inception to November 1, 2018. The study outcomes, including overall survival (OS) and disease-free survival (DFS), were extracted independently by two authors. Results: Fourteen studies involving 3033 patients were evaluated. A meta-analysis of all 14 studies suggested that the OS of the MVI-positive group was significantly worse than that of the MVI-negative group (HR = 2.39, 95% CI = 2.02–2.84, I 2 = 22.8%; P < 0.001). Twelve studies were included in the meta-analysis of DFS, and MVI showed a worse prognosis (HR = 1.79, 95% CI = 1.59–2.02, I 2 = 25.3%; P < 0.001). Subgroup analysis demonstrated that MVI still showed a negative effect on the long-term OS and DFS of patients with solitary small HCC measuring up to 2 cm, 3 cm, or 5 cm. Conclusion: Microvascular invasion was a risk factor for poorer prognosis for solitary small hepatocellular carcinoma.